Hubungan Antara Tingkat Pendidikan, Umur, Paritas, Dan Kadar Hemoglobin Pada Maternal Dengan Kejadian Berat Badan Lahir Rendah (BBLR) Di RS Dr. Oen Surakarta Tahun 2014 - Cahyani, Wahyu, dr. Supanji Raharja, Sp. OG (K), dr. Budi Hernawan (2015)
Background : Low birth weight becomes an important determinant of morbidity and mortality in childhood and child survival. More than 15.5% of 20 million babies are born in the World have low birth weight. There are several factors that contribute low birth weight are a multifactorial it is associated with maternal hemoglobin levels, maternal education level, maternal age, and parity. Methods :This study usesan observational analytic with case controldesign. Sample cases weretaken based on purposive sampling method and simple random control sample from medical record of patients visiting the Dr. Oen Surakarta Hospital in 2014 with 150 samples that met the inclusion criteria. Data being analyzed using Chi Square statistical test and regresi logistic multivariate using SPSS 17 for Windows. Results : Based on bivariate analysis with chi square, statistical test showed that the variables which contributes incidence of low birth weight are the education level with p=<0, 0001 and maternal age with p = 0,047 (p<0,05), and then by performing multivariate analysis with logistic regression test showed that the most variables which contributes the risk of low birth weight is maternal education level with value of OR = 3,46. Conclusion : Low maternal education level is the Risk factor of Low Birth Weight (LBW) incidence.